The effects of diet on circulating sex hormone levels in men. - Allen, N; Key, T (2000)
There is considerable epidemiological evidence that a Western-style diet may increase the risk of certain hormone-dependent conditions in men via its effects on hormone metabolism. Experimental evidence also suggests that dietary factors may exert subtle effects on hormone metabolism. Here we review the clinical and epidemiological evidence that diet is associated with circulating sex hormone levels in men. In comparison with factors such as age and BMI, nutrients do not appear to be strong determinants of sex hormone levels. Dietary intervention studies have not shown that a change in dietary fat and/or dietary fibre intake is associated with changes in circulating sex hormone concentrations over the short term. The data on the effects of dietary phyto-oestrogens on sex hormone levels in men are too limited for conclusions to be drawn. Observational studies between men from different dietary groups have shown that a vegan diet is associated with small but significant increases in sex-hormone-binding globulin and testosterone concentrations in comparison with meat-eaters. However, these studies have not demonstrated that variations in dietary composition have any long-term important effects on circulating bioavailable sex hormone levels in men. This lack of effect may be partly explained by the body's negative feedback mechanism, which balances out small changes in androgen metabolism in order to maintain a constant level of circulating bioavailable androgens. It appears, therefore, that future studies should look for dietary effects on the feedback mechanism itself, or on the metabolism of androgens within the target tissues.